Captive state : the corporate takeover of Britain / George Monbiot. - Monbiot, George, 1963- (Pan, 2001)
George Monbiot made his name exposing the corruption of foreign governments, and now he turns his keen eye on Britain. He uncovers what many have suspected but few have been able to prove, that big business is taking over this country.